Prospect of participatory urban forestry development in Ibadan metropolis, Oyo state, Nigeria (2003)
This study investigated the potential participation of Ibadan residents in the development of urban forestry initiative for environmental rehabilitation of the metropolis. Data were obtained from multi stage randomly sampled 397 residents within the five local government areas (LGAs) in Ibadan metropolis. The result revealed that 49% of the respondents claimed to have trees planted around their residences. Out of this, 83% believed that these trees provide shade for them for recreation, protect their houses from environmental hazards as well as beatify their living environment. It was also discovered that though 84% of the respondents had interest in planting trees, only 78% expressed their willingness to participate in the reforestation of Ibadan metropolis. Furthermore, it was found that such willingness to participate depended significantly on respondents employment status, prior knowledge of existence of Ibadan urban forest reserve, educational level (p < 0.01), and period of residence in the metropolis (p < 0.05). Though several independent variables were not significant in explaining the willingness to participate, the multi-variate logistic regression has a significant likelihood ratio of 24.46 (p < 0.05) and the student’s t-test indicates that only two socio economic variables - age and prior knowledge of existence of the Ibadan urban forest reserves had significant influence (p < 0.05) on the dichotomous willingness to participate in Ibadan urban forestry initiative. The study also identified prospects for both interactive and material participation in this development initiative, whereby 64% of the respondents were willing to pay and participate in some other ways in the programme, while 77% were also willing to join an environmental non-governmental organization that would spearhead this urban reforestation initiative. The results of this study show that urban forestry could be used as development interventions to improve the socio-economic wellbeing of the urban poor, and significantly contribute to cost effectiveness, increased coverage and sustainability of environmental conservation programmes.